2009
DOI: 10.1111/j.1365-2443.2009.01286.x
|View full text |Cite
|
Sign up to set email alerts
|

p97/valosin‐containing protein (VCP) is highly modulated by phosphorylation and acetylation

Abstract: p97/valosin-containing protein (VCP) is a member of the AAA family proteins, which plays various important roles in cells by using its ATPase activity. But mechanism of regulating its ATPase activity is mostly unknown. We report here that VCP is highly modified throughout the protein via acetylation and phosphorylation. In addition to six previously identified phosphorylation sites, we identified at least 14 serines, 14 threonines, 6 tyrosines and 22 lysines as potential modification sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 41 publications
(83 reference statements)
3
40
0
1
Order By: Relevance
“…These sequential modifications were not observed in VCP purified from cells expressing normal lengths of polyglutamines. The same sequential modifications were observed, although less frequently, in purified FLAG-VCP from MG132-treated cells (34). In the absence of MG132 treatment, these sequential modifications were not detected by LC/MS/MS analysis.…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…These sequential modifications were not observed in VCP purified from cells expressing normal lengths of polyglutamines. The same sequential modifications were observed, although less frequently, in purified FLAG-VCP from MG132-treated cells (34). In the absence of MG132 treatment, these sequential modifications were not detected by LC/MS/MS analysis.…”
Section: Resultssupporting
confidence: 52%
“…VCP Modification and Atrophic Phenotypes-We have previously shown that VCP is highly modified by phosphorylation and acetylation (34). We thus purified FLAG-VCP from HEK293T cells expressing expanded polyglutamine tracts, analyzed it by LC/MS/MS, and found that three sequential amino acids, Ser-612, Thr-613, and Lys-614, were modified simultaneously by phosphorylation, phosphorylation, and acetylation, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This residue had already been reported as a site of acetylation [192], but given the modest size discrepancy between lysine acetylation and trimethylation, it is possible that assignment of acetylation to this residue was rather the result of misannotation. The target lysine lies within VCP's first ATPase domain, and it was shown that methylation of this residue results in abrogation of the individual domain's ATPase activity in vitro.…”
Section: Methylationmentioning
confidence: 93%